Chastising Women: A Means to Resolve Marital Problems? - AbdulHamid A AbuSulayman (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2013)
The writer used to find in the declining state of the umma vis-à-vis the surrounding world, the cultural and intellectual attacks against it, and the deteriorating status of human rights of Muslims, all together, as the dilemma which encounters the advocates of Islam and human rights. A notable matter is the ‘chastisement’ of women as a prerogative of the husband and a way to resolve problems of the nuptial association that result from the recalcitrance and disobedience of women and their disaffection for and alienation from their spouses. He was always aware of the reasons and implications of that dilemma, in particular, due to its significance and relevance to the modern world.